Islamic Law and Human Rights: Doctrinal Controversies in Sunni and Shia Islam Since The 1948 Universal Declaration - Setiawan, Iwan; Rifai, Ahmad; Mariana, Mariana (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
From a comparative perspective, this article analyses the doctrinal debate that arose in Sunni and Shia Islam after adopting the Universal Declaration of Human Rights in 1948. This research method is a descriptive comparative prospective study carried out by comparing and explaining the object of research objectively and factually based on the data sources obtained. In this case, the benchmark for comparative data is Islamic law and human rights studies from the perspective of Islamic teachings and Shia Islam. For decades, this text has produced almost no response in Islam. In its final recommendations, the Congress of the Sixth Academy called for uniting the Muslim community, respecting human dignity and human rights, condemning racial discrimination by certain States that believe they are civilized, as well as only publishing works that expose the position of his arguments correspond to the thesis outlined by Abū al-Aʿlā Maudūdī in his texts on the Islamic State and a booklet on human rights in Islam. Certain are confident they are civilized and only publish works that expose the Islamic position on human rights. In November 1975, Mawdūdī gave a lecture in Lahore on the question which arose in response to this recommendation. From the 1980s onwards, more prominent thinkers began to confront their legal traditions with those that became the source of human rights. While comparing the two legal systems contributes to major developments and contrasts in the con-thought of temporary Islamic law.